2007
DOI: 10.1080/01612840701413590
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postpartum Depression and Major Depressive Disorder: Issues in Assessment

Abstract: Postpartum Depression (PPD) is an important social and health problem for women and their families with an incidence of at least 13%. In comparing the diagnosis, timing, and symptom patterns of PPD and Major Depressive Disorder (MDD), there are distinct differences that may partially explain why PPD is under-diagnosed and under-treated. The purpose of this manuscript is to compare and critique the most common instruments used to assess PPD. The Postpartum Depression Screening Scale developed by C.T. Beck and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 57 publications
3
29
0
1
Order By: Relevance
“…The prevalence of PPD in this study, as determined by a self-reported measure of symptoms, was 13.8%. This result aligns with previous studies, which have noted the prevalence of PPD to be between 10% and 15%, with the average being 13% (Evans & Theofrastous, 1997;Miller, 2002;Negus Jolley & Betrus, 2007). The prevalence of PPD diagnosis was 7.6%; however, this measure was only representative of three states and one city, as opposed to the self-reported measure that was more nationally representative.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of PPD in this study, as determined by a self-reported measure of symptoms, was 13.8%. This result aligns with previous studies, which have noted the prevalence of PPD to be between 10% and 15%, with the average being 13% (Evans & Theofrastous, 1997;Miller, 2002;Negus Jolley & Betrus, 2007). The prevalence of PPD diagnosis was 7.6%; however, this measure was only representative of three states and one city, as opposed to the self-reported measure that was more nationally representative.…”
Section: Discussionsupporting
confidence: 92%
“…PPD is divided into three categories: 1) The blues, which affect roughly 50% to 80% of new mothers and is considered to be normal, 2) nonpsychotic PPD, which affects roughly 10% to 15% of new mothers, with the incidence being on average 13%, and 3) postpartum psychosis, which is rarer than the other two types and occurs in roughly one or two out of every thousand pregnancies (Evans & Theofrastous, 1997;Miller, 2002;Negus Jolley & Betrus, 2007;O'Hara & Swain, 1996).…”
mentioning
confidence: 99%
“…A number of these existing reviews of depression scales did not include more recent validation studies (Boyd et al, 2005;DeRosa & Logsdon, 2006;Gaynes et al, 2005;Jolley & Betrus, 2007) or focused on only a limited set of three or four scales (King, 2012;Zubaran et al, 2010). Thus, our review is more timely and comprehensive.…”
Section: Depressionmentioning
confidence: 91%
“…Still, several reviews are noteworthy. In the psychosocial realm, one set of reviews focused specifically on measurement of perinatal or postpartum depression and compared psychometric properties of four to eight scales for measuring depressive symptoms or screening for depression (Boyd, Le, & Somberg, 2005;DeRosa & Logsdon, 2006;Gaynes et al, 2005;Jolley & Betrus, 2007;King, 2012;Zubaran, Schumacher, Roxo, & Foresti, 2010). However, many of these reviews do not include recent postpartum validation studies.…”
mentioning
confidence: 98%
“…One recent meta-analysis found the mean prevalence of post-partum depression ranged from 1 per cent to 57 per cent (Gaynes 2005, cited in Negus Jolley andBetrus 2007). Post-partum depression has been thought to be under-diagnosed and undertreated because of several factors, including lack of background knowledge about the post-partum period on the part of mental health and primary care providers, a lack of agreement among professionals on whether post-partum depression is just a normal depression during the postnatal period or a unique disorder, and the shame associated with depression at a time when women are supposed to be happy (Beck and Gable 2000 as cited in Negus Jolley and Betrus 2007).…”
Section: Problems In Defining Post-partummentioning
confidence: 97%